Administrative law and intellectual movement in the reign of Sultan Alauddin Mansur Shah of the 16th century in Aceh - KHAIRUL NIZAM BIN ZAINAL BADRI (Rihlah : Jurnal Sejarah dan Kebudayaan, 2021)
Sultanate of Aceh is recognized as one of the most important Malay-Muslim kingdom of the past, especially after the fall of the Malacca Sultanate in the 16th century AD. From a large number of its rulers, Aceh was ruled by a king's daughter who came from abroad. One of them was Sultan Alauddin Mansur Shah who hails from Perak located on the Malay Peninsula. But to be presented in this paper is not about the origins of his coming from the state, but rather a contribution to the development of Aceh, especially in the field of knowledge. The study is based on qualitative methods, using data from the writing of the history of Aceh are then analyzed to assess and justify his stature. What can be summed up is that his services as one of the important figures in nurturing the culture of knowledge and religious teachings cannot be ignored. It is very important if more research on it is done in the future in line with the efforts to excavate the treasures of the past so that the historical aspect is always fresh with positive values.